Nanoencapsulation and Nanocoating of Bioactives of Application Interest in Food, Nutraceuticals and Pharma - Cristina Prieto; Jose M. Lagaron (Nanomaterials, 2024)
Bioactives are functional molecules that pose several challenges, including poor solubility, low permeability, and low chemical, biochemical, or process stability, resulting in reduced functionality and bioavailability [...]